DETERMINATION OF THE EPHEMERIS ACCURACY FOR AJISAI, LAGEOS AND ETALON SATELLITES, OBTAINED WITH A SIMPLIFIED NUMERICAL MOTION MODEL USING THE ILRS COORDINATES - Kara, I. V. (Одеські астрономічні публікації, 2013)
This paper describes a simplified numerical model of passive artificial Earth satellite (AES) motion. The model accuracy is determined using the International Laser Ranging Service (ILRS) highprecision coordinates. Those data are freely available on http://ilrs.gsfc.nasa.gov. The differential equations of the AES motion are solved by the Everhart numerical method of 17th and 19th orders with the integration step automatic correction. The comparison between the AES coordinates computed with the motion model and the ILRS coordinates enabled to determine the accuracy of the ephemerides obtained. As a result, the discrepancy of the computed Etalon-1 ephemerides from the ILRS data is about 10″ for a one-year ephemeris.